Inscriptions on the Hero Stone - Temples of India Project Team (Jio Institute, 2024)
The hero stone slabs feature depictions of human figures in the upper half, while the lower half shows faint traces of inscriptions. Though illegible, closer examination suggests the inscription were likely written in the Devnagari script. The content of the inscription remains unknown, but typically inscriptions on hero stones detail of the deceased and the time of the craving. Palaeographically, the script can tentatively be placed within a broad timeframe from 12th to 15th centuries CE. However, due to the deteriorated condition of the stone slabs, no definitive conclusions can be drawn.